Neonatal Screening for Congenital Adrenal Hyperplasia in Turkey: A Pilot Study with 38,935 Infants - GÜRAN, TÜLAY (GALENOS YAYINCILIK, 2019)
Objective: Congenital adrenal hyperplasia (CAH) is the most common form of primary adrenal insufficiency in children. Neonatal screening for CAH is effective in detecting the salt-wasting (SW) form and in reducing mortality. in this study, our aim was to estimate the incidence of CAH in Turkey and to assess the characteristics and efficacy of the adopted newborn CAH screening strategy. Methods: A pilot newborn CAH screening study was carried out under the authority of the Turkish Directorate of Public Health. Newborn babies of >= 32 gestational weeks and >= 1500 gr birth weight from four cities, born between March 27-September 15, 2017 were included in the study. Screening protocol included one sample two-tier testing. In the first step, 17 alpha-hydroxyprogesterone (17-OHP) was measured by fluoroimmunoassay in dried blood spots (DBS) obtained at 3-5 days of life. The cases with positive initial screening were tested by steroid profiling in DBS using a liquid chromatography-tandem mass spectrometry method to measure 17-OHP, 21-deoxycortisol (21-S), cortisol (F), 11-deoxycortisol and androstenedione as a second-tier test. The babies with a steroid ratio (21-S + 17-OHP)/F of >= 0.5 were referred to pediatric endocrinology clinics for diagnostic assessment. Results: 38,935 infants were tested, 2265 (5.82 %) required second-tier testing and 212 (0.54 %) were referred for clinical assessment, six of whom were diagnosed with CAH (four males, two females). Four cases were identified as SW 21-hydroxylase deficiency (21-OHD) (two males, two females). One male baby had simple virilizing 21-0HD and one male baby had II-OHD CAH. The incidence of classical 21-0HD in the screened population was 1:7,787. Conclusion: The incidence of CAH due to classical 21-OHD is higher in Turkey compared to previous reports. We, therefore, suggest that CAH be added to the newborn screening panel in Turkey. The use of steroid profiling as a second-tier test was found to improve the efficacy of the screening and reduce the number of false-positives.
Keywords: Newborn screening; congenital adrenal hyperplasia; second-tier; steroid profiling; TANDEM MASS-SPECTROMETRY; 21-HYDROXYLASE DEFICIENCY; STEROID PROFILE; BLOOD; 21-DEOXYCORTISOL; PREVALENCE; MUTATIONS; PROGRAM